2020
DOI: 10.1016/j.jgg.2020.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Engineering T cells for immunotherapy of primary human hepatocellular carcinoma

Abstract: Liver cancers, majority of which are primary hepatocellular carcinoma (HCC), continue to be on the rise in the world. Furthermore, due to the lack of effective treatments, liver cancer ranks the 4 th most common cause of male cancer deaths. Novel therapies are urgently needed. Over last few years, immunotherapies, especially the checkpoint blockades and adoptive cell therapies of engineered T cells, have demonstrated a great potential for treating malignant tumors including HCC. In this review, we summarize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 164 publications
0
12
0
Order By: Relevance
“…, cluster of differentiation 28 [CD28], 4-1BB, and CD134). Then the activated T cells rapidly perform immune functions to kill targeted cells[ 93 - 95 ]. Unrestricted by major histocompatibility complex (MHC), CAR-T cells can directly recognize tumor cells and avoid the immune-evasion mechanism of tumor cells via down-regulation of MHC[ 96 ].…”
Section: Potential Immunotherapeutic Innovationsmentioning
confidence: 99%
See 2 more Smart Citations
“…, cluster of differentiation 28 [CD28], 4-1BB, and CD134). Then the activated T cells rapidly perform immune functions to kill targeted cells[ 93 - 95 ]. Unrestricted by major histocompatibility complex (MHC), CAR-T cells can directly recognize tumor cells and avoid the immune-evasion mechanism of tumor cells via down-regulation of MHC[ 96 ].…”
Section: Potential Immunotherapeutic Innovationsmentioning
confidence: 99%
“…Several HCC-related antigens targeted by TCR have been identified, e.g. , AFP-, GPC3-, virus-, NY-ESO-1-, and hTERT-specific TCRs[ 95 ]. Despite the success of NY-ESO-1-targeted TCR-T cells to treat multiple myeloma and synovial sarcoma, recent studies about TCR-T for HCC focus on targeting AFP[ 95 ].…”
Section: Potential Immunotherapeutic Innovationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that engineered T cells engrafted with antigen-specific receptors may induce major histocompatibility complex (MHC)-independent immune responses that efficiently enhance anti-tumor immunity and cytokine production [ 5 ā€“ 7 ]. Chimeric antigen receptors (CARs) are constructed by linking the variable regions of the heavy and light chains of an antibody specific for a tumor cell surface molecule to the intracellular activation domain of the T-cell receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, limited early symptoms in HCC patients could lead to delayed diagnoses, which greatly undermines the survival outcomes of HCC patients ( Sun et al, 2020 ). For patients with advanced stage HCC, whose conditions are usually not suitable for surgical resection, immunotherapies are considered as an effective and promising strategy ( Caraballo Galva et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%